1999
DOI: 10.1002/(sici)1521-3935(19990101)200:1<25::aid-macp25>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of styrene with CO catalysed by palladium‐substituted 1,10‐phenanthroline bis(methoxycarbonyl) complexes [Pd(L—L)(COOMe) 2 ]

Abstract: SUMMARY: A new class of highly effective homogeneous palladium bis(methoxycarbonyl) complexes Pd(L1L)(COOMe) 2 , where (L1L) are substituted phenanthroline ligands, has been developed for the production of syndiotactic alternating styrene-carbon monoxide copolymers. The essential feature of this novel catalytic system is that it is formed by palladium complex, Pd(L1L)(COOMe) 2 , an acid cocatalyst, (L1L)HPF 6 , bearing a weakly coordinating counter anion, and an oxidant, such as 1,4-naphthoquinone (1,4-NQ). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…In addition, if such a system contains electric charge on the extended coplanar moiety, it may show additional interaction with nucleic acid (Scheme 1). Several Pd (II) complexes with phen have been reported [11][12][13][14][15][16], and some of them have revealed potential anti-tumor activity towards different cell lines which are equal to or more than the activity of cisplatin. However, there are few reports concerning DNA-binding of the 1,10-phenanthroline palladium (II) complexes of dithiocarbamates [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, if such a system contains electric charge on the extended coplanar moiety, it may show additional interaction with nucleic acid (Scheme 1). Several Pd (II) complexes with phen have been reported [11][12][13][14][15][16], and some of them have revealed potential anti-tumor activity towards different cell lines which are equal to or more than the activity of cisplatin. However, there are few reports concerning DNA-binding of the 1,10-phenanthroline palladium (II) complexes of dithiocarbamates [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…Few reports have appeared on the use of substituted phenanthroline ligands and they mainly concern the commercially available, methyl‐containing phenanthrolines. For instance, we5 and others6 reported that a remarkable decrease in the activity is found with the monochelated carboxylato Pd derivatives, [Pd(RCOO) 2 (N–N)] (R = Me, CF 3 ), on going from phen to 4,7‐dimethyl‐1,10‐phenanthroline (4,7‐Me 2 ‐phen), to 3,4,7,8‐tetramethyl‐1,10‐phenanthroline (Me 4 ‐phen), to 2,9‐dimethyl‐1,10‐phenanthroline (2,9‐Me 2 ‐phen), the latter being completely inactive. The influence of the ligand is even more pronounced when the bischelated complexes, [Pd(N–N) 2 ][PF 6 ] 2 , are used (N–N = phen, 4,7‐Me 2 ‐phen, Me 4 ‐phen) 3d.…”
Section: Introductionmentioning
confidence: 99%
“…The productivity was higher than is typically observed with this catalyst system in methanol under similar conditions (0.6-2.2 kg CP (g Pd) 21 ). 16,20 Copolymers produced in [C 6 pyr][NTf 2 ] also had higher molecular weights (M n = 25000) than are obtained in methanol. 20,21 The polydisperities of the copolymers were narrow (1.3-2.5) suggesting a single-site catalyst.…”
mentioning
confidence: 99%
“…16,20 Copolymers produced in [C 6 pyr][NTf 2 ] also had higher molecular weights (M n = 25000) than are obtained in methanol. 20,21 The polydisperities of the copolymers were narrow (1.3-2.5) suggesting a single-site catalyst. The isolated copolymers were pale yellow rather than the grey polymer produced in MeOH.…”
mentioning
confidence: 99%